Impact of Extreme Obesity and Diet‐Induced Weight Loss on the Fecal Metabolome and Gut Microbiota. Issue 5 (7th October 2020) - Nogacka, Alicja M.; de los Reyes‐Gavilán, Clara G.; Martínez‐Faedo, Ceferino; Ruas‐Madiedo, Patricia; Suarez, Adolfo; Mancabelli, Leonardo; Ventura, Marco; Cifuentes, Alejandro; León, Carlos; Gueimonde, Miguel; Salazar, Nuria
Abstract : Scope: A limited number of human studies have characterized fecal microbiota and metabolome in extreme obesity and after diet‐induced weight loss. Methods and results: Fecal samples from normal‐weight and extremely obese adults and from obese participants before and after moderate diet‐induced weight loss are evaluated for their interaction with the intestinal adenocarcinoma cell line HT29 using an impedance‐based in vitro model, which reveals variations in the interaction between the gut microbiota and host linked to obesity status. Microbiota composition, short chain fatty acids, and other intestinal metabolites are further analyzed to assess the interplay among diet, gut microbiota, and host in extreme obesity. Microbiota profiles are distinct between normal‐weight and obese participants and are accompanied by fecal signatures in the metabolism of biliary compounds and catecholamines. Moderate diet‐induced weight loss promotes shifts in the gut microbiota, and the primary fecal metabolomics features are associated with diet and the gut–liver and gut–brain axes. Conclusions: Analyses of the fecal microbiota and metabolome enable assessment of the impact of diet on gut microbiota composition and activity, supporting the potential use of certain fecal metabolites or members of the gut microbiota as biomarkers for the efficacy of weight loss in extreme obesity. Abstract : Shifts in gut microbiota and fecal metabolome features associated with the metabolism of biliary compounds and catecholamines are observed between normal weight (NW) and extremely obese (OB) individuals. Moderate weight loss after diet (OB.2) promotes changes in the gut microbiota whereas the fecal metabolomic profile is mainly associated with dietary changes and with the gut‐liver and gut‐brain axes.